A framework to nurturing digital entrepreneurs: Demystifying critical factors that influence tech-driven business behavior - Elissa Dwi Lestari; Florentina Kurniasari; D. Wim Prihanto; Angely Maylin (Problems and Perspectives in Management)
Technology and the internet have altered business activities by enabling organizations to reach customers, develop markets, enhance profitability, and raise brand awareness. With 167 million social media users, Indonesia’s internet economy provides numerous entrepreneurial possibilities; however, just 0.43% of entrepreneurs are technology-based. This demonstrates the need for digital entrepreneurship education and effective social media use, particularly among tech-savvy college students. The present study aims to examine the effects of social media utilization, digital entrepreneurship education, and attitude toward digital business on the technology-based entrepreneurial behavior of Indonesian university students, using the frameworks of the unified theory of acceptance and use of technology and the theory of planned behavior. This study employs quantitative research using a non-probability sampling method with a judgmental technique, focusing on 391 university students engaged in entrepreneurial activities using social media. The study employed SmartPLS to analyze the research data. The results indicate that social influence, work and performance expectations, and attitude toward digital entrepreneurship positively influence the use of social media for technology-based entrepreneurial activities. Moreover, the paper unveiled that the provision of digital entrepreneurship education and the utilization of social media for commercial purposes had a beneficial influence on behavior that is predisposed toward technology. The present study demonstrates that the adoption of social media functions as a mediator in the association between digital entrepreneurship education and the adoption of social media, therefore exerting an impact on technology-based entrepreneurial behavior. AcknowledgmentsThe research team would like to thank the Ministry of Education, Research and Technology of the Republic of Indonesia for providing funding for the research program based on Decree number 0667/E5/AL.04/2024 with university internal decree number: 0038-RD-LPPM-UMN/P-HD/VI/2024, and Universitas Multimedia Nusantara for supporting the implementation of this investigation.